Australia–Indonesia Economic Relations Under IA-CEPA: Between Proximity and Distance - Fathana, Hangga; Mulia, Jalaluddin Rizqi (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2025)
This article examines the extent to which the Indonesia–Australia Comprehensive Economic Partnership Agreement (IA-CEPA) has contributed to strengthening bilateral relations. It argues that despite geographic proximity, trade ties remain weak and IA-CEPA alone is unlikely to generate long-term mutual benefits. Employing an interpretivist qualitative interpretivist approach, the study draws on government reports and policy documents to analyze negotiation dynamics and outcomes. The article introduces an actor-centered perspective, showing how limited civil society involvement has constrained the agreement’s potential. It argues that IA-CEPA is unlikely to provide long-term mutual benefits unless the government of the two countries provides a more comprehensive approach to public diplomacy. The findings suggest that without stronger political leadership and more inclusive public diplomacy, IA-CEPA will deliver suboptimal results. The study highlights the need for people-to-people engagement as a bridge-builder for sustainable cooperation.